Фондовий ринок України: сучасний стан - Янковська, В. А.; Шум (Семенець), Аліна Олександрівна; Чемчикаленко, Р. А. (НТУ "ХПІ", 2015)
У статті розглянуто основні показники діяльності фондового ринку на сучасному етапі його розвитку, висвітлені деякі проблеми його функціонування та запропоновані перспективи розвитку та стратегії інтегрування у міжнародні ринки. Показано, що інтеграція з Європейським Союзом дозволить Україні спростити процедуру розміщення вітчизняних цінних паперів за кордоном і сприятиме зменшенню надмірного податкового навантаження на суб’єкти господарювання в Україні.

The article considers main performance measures of the stock market on the present stage of its development. It is made the assessment and found problems of functioning of the stock market of Ukraine. It is proved that Ukraine has enough economic potential for building of national stock market which growth rate will outstrip the dynamics of the gross domestic product. It is investigated that convergence of existing and future legislation of Ukraine with international standards is a very important condition for achieving the attractiveness of securities markets of Ukraine for investors. This path should provide a real opportunity to integrate Ukrainian securities market to international markets. It is grounded the ways of improvement of its development and European integration. Some problems of its functioning, perspectives of its improvement and integration strategies in international markets are also covered. It is proved that the integration with the European Union is a very important stage for Ukrainian stock market development and it will simplify placement of domestic securities abroad procedure and also will contributereducing the excessive tax burden on business entities in Ukraine.
The stock market of Ukraine:the current condition
Keywords: міжнародні ринки; цінні папери; фондова біржа; податкове навантаження; stock market; securities; stock exchange